Guanidinoacetate (GAA) is a potent GABA(A) receptor GABA mimetic: Implications for neurological disease pathology - Meera Pratap; Uusi-Oukari Mikko; Wallner Martin; Lipshutz Gerald S (Wiley, 2026)
Impairment of excretion and enzymatic processing of nitrogen, for example, because of liver or kidney failure, or with urea cycle and creatine synthesis enzyme defects, surprisingly leads to primarily neurologic symptoms, yet the exact mechanisms remain largely mysterious. In guanidinoacetate N-methyltransferase (GAMT) deficiency, the guanidino compound guanidinoacetate (GAA) increases dramatically, including in the cerebrospinal fluid (CSF), and has been implicated in mediating the neurological symptoms in GAMT-deficient patients. GAA is synthesized by arginine-glycine amidinotransferase (AGAT), a promiscuous enzyme that not only transfers the amidino group from arginine to glycine, but also to primary amines in, for example, GABA and taurine to generate gamma-guanidinobutyric acid (γ-GBA) and guanidinoethanesulfonic acid (GES), respectively. We show that GAA, γ-GBA, and GES share structural similarities with GABA, evoke GABAA receptor (GABAAR) mediated currents (whereas creatine [methylated GAA] and arginine failed to evoke discernible currents) in cerebellar granule cells in mouse brain slices and displace the high-affinity GABA-site radioligand [3H]muscimol in total brain homogenate GABAARs. While γ-GBA and GES are GABA agonists and displace [3H]muscimol (EC50/IC50 between 10 and 40 μM), GAA stands out as particularly potent in both activating GABA(A)Rs (EC50 ~ 6 μM) and also displacing the GABAAR ligand [3H]muscimol (IC50 ~ 3 μM) at pathophysiologically relevant concentrations. These findings stress the role of substantially elevated GAA as a primary neurotoxic agent in GAMT deficiency and we discuss the potential role of GAA in arginase (and creatine transporter) deficiency which show a much more modest increase in GAA concentrations yet share the unique hyperexcitability neuropathology with GAMT deficiency. We conclude that orthosteric activation of GABAARs by GAA, and potentially other GABAAR mimetic guanidino compounds (GCs) like gamma-GBA and GES, interferes with normal inhibitory GABAergic neurotransmission which could mediate, and contribute to, neurotoxicity.